The Politics of "Queer Reading" an Ethiopian Saint and Discovering Precolonial Queer Africans. - Debele, Serawit (Journal of African Cultural Studies, 2022)
This article asks what it means to discover Africans through our sexual desires, and how that might shape the way the West knows both women and queer people. I closely read Wendy Belcher's interpretations of the sexual life of Wälättä P̣eṭros, a seventeenth-century Ethiopian female saint. While the article draws on postcolonial, African feminist and queer scholarship, it takes a cue from Saidiya Hartman's "Venus in Two Acts" to raise speculative questions related to the opacity of the text. I argue that Belcher's interpretation of carnal desire produces the saint as a hysterical subject, and attaches to the saint's life the claim of discovering queer people in pre-colonial Africa. I argue that this interpretation assimilates the saint into our contemporary ideas of sexuality and thereby invents a modern subject through a reading that is divorced from historical and geographic specificities. The article also explores the benevolent intentions of discovering pre-colonial queer Africans for the cause of present-day struggles against persecution. It is not my intention here to discount the translation of the hagiography, nor is it to dispute the possibilities of reading same-sex intimacies. I am interested in thinking about the presentist preoccupations of the interpretation.